The Herbal Compound Thymol Targets Multiple Salmonella Typhimurium Virulence Factors for Lon Protease Degradation - Yong Zhang; Yong Zhang; Yan Liu; Jingjing Luo; Jing Jie; Xuming Deng; Lei Song (Frontiers Media S.A., 2021)
Many important bacterial pathogens are using the type III secretion system to deliver effectors into host cells. Salmonella Typhimurium (S. Typhimurium) is a pathogenic Gram-negative bacterium with the type III secretion system as its major virulence factor. Our previous studies demonstrated that thymol, a monoterpene phenol derivative of cymene, inhibited S. Typhimurium invasion into mammalian cells and protected mice from infection. However, the antibacterial mechanism of thymol is not clear. In this study, we revealed that thymol interferes with the abundance of about 100 bacterial proteins through proteomic analysis. Among the 42 proteins whose abundance was reduced, 11 were important virulence factors associated with T3SS-1. Further analyses with SipA revealed that thymol directly interacts with this protein to induce conformational changes, which makes it susceptible to the Lon protease. In agreement with this observation, thymol effectively blocks cell invasion by S. Typhimurium. Thus, thymol represents a class of anti-virulence compounds that function by targeting pathogenic factors for degradation.